Teaching of the Nervous System and Perceptions of Neuromyths in Teachers: Enseñanza del sistema nervioso y percepciones de los neuromitos en el profesorado (2021)
Introduction: The lack of articulation of neurosciences to educational processes gave rise to a series of misconceptions known as Neuromyths, these fallacies can be assumed by critical formal ignorance of the way the nervous system works. This text intends to describe in the first place aspects of the teaching of the human nervous system and the perceptions about the neuromyths that Natural Sciences teachers have in basic education. Methodology: for this, an online survey was applied to 20 Natural Sciences teachers who work in Basic Education in the Colombian context. Results and discussion: It was found that most teachers address the contents of the nervous system from the exploration of previous knowledge to the development of complex processes of anatomy and physiology. On the other hand, although most teachers do not agree with the neuromyths raised, they still persist: critical periods, hemispheric dominance and the use of 10 % of the brain. In this sense, it is recognized that the prevalence of neuromyths in teachers can have repercussions on educational processes and evidences the gap that still exists between neuroscience and education. Conclusions: According to the above, it is necessary that teacher training programs and educational institutions open spaces for critical reflection that allow teachers and teaching directors to access information related to scientific and technological advances between neuroscience and education.